A conjugated polymer‐liposome complex: A contiguous water‐stable, electronic, and optical interface. Issue 1 (21st November 2020) - Jephcott, Lilli; Eslami, Minoo; Travaglini, Lorenzo; Lauto, Antonio; Mawad, Damia
Abstract: The electronic and optical properties of conjugated polymers and conjugated polyelectrolytes have attracted considerable research interest across a broad range of applications. Interfacing them with the lipid bilayer enables the engineering of interfaces with unique characteristics, facilitated by accessing the properties of each constituent material. Research done on these interfaces tap into a broad range of applications. Fundamental studies have been conducted to gain insight into the polymer interaction with a lipid membrane that mimics the biological cell. Bioimaging and biosensing devices have been developed, exploiting optical and superquenching properties of the polymer. Delivery systems based on these complexes were applied in photothermal therapy using the polymer high thermal conversion efficiency. This minireview presents a summary of this research, highlighting that while the field remains in its early development, conjugated polymer/polyelectrolyte interfaces hold huge potential for biomedical applications. Abstract : Coupling conjugated polymers with liposomes allows the engineering of interfaces with unique characteristics, enabled by accessing the properties of each constituent material. This Mini‐Review presents advancements made in the development of conjugated polymer‐liposome complexes. While the field remains in its early development, studies reported to date indicate that these complexes are poised to make an impact in the biomedical field.